2017
DOI: 10.1016/j.parkreldis.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Crohn's disease with Parkinson’s disease

Abstract: We retrospectively investigated the co-occurrence of Crohn's disease in a cohort of 876 patients with Parkinson's disease, based on the observation that LRRK2 is a shared genetic risk factor. We identified 2 patients with Crohn's disease; this number was consistent with the number of cases expected in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 5 publications
2
12
1
Order By: Relevance
“…Another retrospective study by Fujioka et al investigated the occurrence of CD with PD by searching the medical records of 876 PD patients and subsequently looked for incidences of prior or cur-rent CD. The study found that the co-occurrence of CD with PD was consistent with the number of cases expected in the general population [61]. However, limitations to this study was the relatively small number of subjects.…”
Section: Epidemiological Evidence For a Link Between Ibd And Pdsupporting
confidence: 82%
“…Another retrospective study by Fujioka et al investigated the occurrence of CD with PD by searching the medical records of 876 PD patients and subsequently looked for incidences of prior or cur-rent CD. The study found that the co-occurrence of CD with PD was consistent with the number of cases expected in the general population [61]. However, limitations to this study was the relatively small number of subjects.…”
Section: Epidemiological Evidence For a Link Between Ibd And Pdsupporting
confidence: 82%
“…In the Swedish study, patients with IBD who did not receive treatment were 60% more likely to develop PD than their matched controls, whereas treated IBD patients had a nonsignificantly decreased risk of developing PD compared to nontreated patients [89]. However, a retrospective study enrolling 876 patients with PD identified only 2 patients with CD prior to the PD diagnosis, an incidence similar to that in the general population [91]. Another large population-based, case–control study enrolling patients aged 65 years or older with newly diagnosed PD ( n = 89,790) and controls ( n = 118,095) identified an inverse correlation between PD and IBD, suggesting that patients with IBD are less likely to develop PD [90].…”
Section: Mechanism Of Gi Impairment and Gut Pathology In Pdmentioning
confidence: 99%
“…Nothing has been published on this subject for the next 20 years but the genetic overlap between PD and CD relaunched the debate. While a small monocentric retrospective study did not observe any increased occurrence of CD in PD patients [11], four large nationwide surveys showed that IBD patients had an increased risk of subsequent PD compared to controls [12][13][14][15] ( table 1). After combining the data of these four studies, a recent meta-analysis showed that the overall risk of PD in IBD was significantly higher than controls (relative risk 1.41, 95% confidence interval:…”
Section: Pd and Ibd Are Epidemiologically Linkedmentioning
confidence: 99%